Sulfate durability and leaching behaviour of dry- and wet-mix shotcrete mixes. (November 2020) - Steindl, Florian R.; Galan, Isabel; Baldermann, Andre; Sakoparnig, Marlene; Briendl, Lukas; Juhart, Joachim; Thumann, Maria; Dietzel, Martin; Röck, Rudolf; Kusterle, Wolfgang; Mittermayr, Florian
Abstract: Shotcrete is a material frequently used in underground constructions such as tunnels, where Ca leaching and sulfate attack are important durability issues. In this study, two test methods were employed to investigate the sulfate resistance and leaching behaviour of dry- and wet-mix shotcretes in sulfate solutions on a time-resolved basis. Tests on powdered samples showed the dissolution of AFm, portlandite and C-A-S-H, subsequently followed by the precipitation of calcite and ettringite. The extent of sulfate expansion of drill cores corresponded to the chemical response of the powder materials, particularly on the reactivity of Ca- and Al-containing hydrated cement phases. The use of high-purity metakaolin (7–10 wt%) in the shotcrete binder significantly decreased the sulfate durability, while high amounts of other SCMs such as blast-furnace slag and silica fume (>20 wt%) had a positive effect on the durability of shotcrete. Highlights: New insights to leaching and sulfate durability of dry- and wet-mix shotcrete Additions of SCMs significantly change durability behaviour. Expansion corresponds to chemical changes during sulfate attack. Shotcrete with low-sulfated binder takes up more sulfate.